PENGARUH HEAD DAN LUAS UNDERFLOW TERHADAP EFISIENSI PEMISAHAN SEDIMEN HYDROCYCLONE - Rahmawati, Debby; Santosa, Budi (Universitas Gunadarma, 2014)
Hydrocyclone is a tool used for the separation of solid materials in the carrier medium by utilizing the generated vortex effect of centrifugal force. Hydrocyclone consists of a vertical cylindrical portion with a funnel-shaped bottom part, inlet doors on the upper side, the door at the bottom of the underflow and overflow at the top of the door. In this study will be known how widespread the effect of head and underflow of the water in the sediment separation efficiency hydrocyclone apparatus. Variations on hydrocyclone efficiency of 94.1% due to the broad head and underflow and the remaining 5.9% is influenced by other things that can not be explained by existing variables. Between the head and sediment hydrocyclone separation efficiency are unidirectional relationship but weak. Wide underflow with sediment hydrocyclone separation efficiency occurs negative correlation is very strong and has a closeness, while the head and broad underflow there is no relationship. The best analysis model in predicting the dependent variable (sediment hydrocyclone separation efficiency) with the influence of the independent variables (head and broad underflow) is a multiple linear regression model with a predictive equation Y = 0612 + 0915 head - spacious 0646 underflow. Prediction efficiency hydrocyclone separation highest sediment that occurs at 98 746% with the results of laboratory studies of 99 781%, which is at the head of 50% and 13% of the underflow broad inlet door. Key words: hydrocyclone, head, broad underflow, the separation efficiency of the sediment, and water